Fear of Death and Sleep Quality in the Aftermath of an Earthquake - Aktura, Seher Cevik; Celik, Hanife; Saritas, Seyhan Citlik; Ozden, Gurkan (Slack Inc, 2025)
PURPOSE: To examine fear of death and disruption in sleep patterns in individuals who have experienced an earthquake. METHOD: A descriptive and relationship-oriented study was performed with 322 individuals who experienced the February 6, 2023, earthquake in Turkey. Data were collected between February 20 and May 15, 2023. A personal information form, the Pittsburgh Sleep Quality Index (PSQI), and Death Anxiety Scale (DAS) were used for data collection. RESULTS: Participants'mean DAS score was 7.96 (SD = 1.05), and mean PSQI score was 8.74 (SD = 4.06). Statistically significant relationships were found between sex, marital status, and mean DAS score, and these variables accounted for 11.7% of the total variance. Similarly, statistically significant relationships were found among economic status, relationship to person trapped under the rubble, financial loss from the earthquake, and mean PSQI score, accounting for 11.3% of the total variance. Women and married people had greater fear of death, and those with good economic status, whose family members were buried under rubble, and who experienced financial loss as a result of the earthquake had lower sleep quality. CONCLUSION:The earthquake led to moderate fear of death and poor sleep quality among participants. Findings highlight the need for targeted support for vulnerable groups following disasters. [Journal ofPsychosocial Nursing and Mental Health Services, 63(2), 45-54.]
Keywords: Validation; Survivors; Exposure; Anxiety